Everyone communicates, few connect what the most effective people do differently - Maxwell, John C. (Thomas Nelson, 2010)
The world's most respected leadership expert gives five principles and five practices for breaking the invisible barrier to leadership and personal success.You have a good idea but can't convince your peers of its merit. You crafted a groundbreaking strategy, but the team trudges on in the same old way. Certain people move forward in their career while you seem to be stuck. If this describes you or someone you know, the problem is not the quality of what you have to offer. The problem is how you connect with people to create the results you desire.In Everyone Communicates, Few Connect, John Maxwell takes readers through the Five Connecting Principles and the Five Connecting Practices of top-notch achievers. He believes that a person's ability to create change and results in any organization-be it a company, church, nonprofit, or even a family-is directly tied to the ability to use the teachings of this book
Keywords: Business communication